Poly(vinylidene fluoride)/modified calcium carbonate nanoparticle hollow fiber membranes for carbon dioxide removal - Kofal, Fosi Mohamoud (2020)
The principal aim of this research work is to compensate for the shortcomings, especially pore wetting and mass transfer resistance, of polymeric membrane materials employed for carbon dioxide (CO2) removal via gas-liquid membrane contactors. Calcium carbonate (CaCO3) nanoparticles hydrophobically modified with octadecyl dihydrogen phosphaste were embedded in the polymer matrices to develop mixed matrix membranes (MMMs) with a well-tailored structure. Porous hydrophobic polyvinylidene fluoride (PVDF) mixed matrix hollow fiber membranes were fabricated via phase inversion method by incorporating CaCO3 nanoparticles in various mixing ratios (10/100, 20/100 and 30/100 CaCO3/PVDF). The effects of CaCO3 nanoparticle loadings on the morphology, structure, and performance of the MMMs were investigated. The addition of CaCO3 nanoparticles enhanced the surface roughness, permeation rate, porosity, and wettability resistance of the MMMs. Peak CO2 absorption performance of 1.52 × 10-3 mol m-2 s-1 at 300 ml/min absorbent flow rate was achieved when 20/100 weight ratio of CaCO3/PVDF was employed. However, further increase of the ratio resulted in MMMs with lower absorption performance. Moreover, a long-term stability study of the MMMs with the best CO2 absorption flux showed no decline in performance in the initial 210 hours of operation, indicating the significant improvement caused by the addition of CaCO3 nanoparticles into polymer matrix. From the physical CO2 stripping tests point of view, similar trend of results were obtained. It was found that the CO2 highest stripping flux of 1.8 × 10-2 mol m-2 s-1 and efficiency of 67% were achieved when 20/100 mixing ratio of CaCO3/PVDF was employed, corresponding to its high gas permeation and effective surface porosity. For the purpose of further optimization, polymer concentration in dope solution was varied to study its effect on membrane characteristics. After the selection of MMM with the best CO2 removal performance (in this case 20/100 CaCO3/PVDF membrane), the MMMs with various polymer concentrations (16, 17, 18, and 19 wt.% PVDF) were prepared. Improvements in porosity and nitrogen permeance were recorded for P17, the MMM with 17 wt.% polymer concentration. Superior CO2 absorption performance of 1.66 × 10-3 mol m-2 s-1 at 300 ml/min absorbent flow rate was also recorded. Moreover, testing P17 at various operating temperatures during CO2 stripping process ranging from 27 °C to 100 °C was carried out. The maximum stripping flux of 2.57 × 10-2 mol m-2 s-1 at 2.3 m s-1 liquid velocity and 80 °C absorbent temperature was higher than the fluxes of the compared in-house and commercial membranes. Henceforth, the enhanced porosity of P17 coupled with its high wetting resistance suggests its potential for the efficient removal of CO2 via gas-liquid membrane contactors.